Cyanidin-3-rutinoside acts as a natural inhibitor of intestinal lipid digestion and absorption - Thavaree Thilavech; Sirichai Adisakwattana (BMC, 2019)
Abstract Background Cyanidin-3-rutinoside (C3R), a naturally occurring anthocyanin, possesses anti-oxidant, anti-hyperglycemic, anti-glycation and cardioprotective properties. However, its mechanisms responsible for anti-hyperlipidemic activity have not been fully identified. The aim of the study was to investigate the lipid-lowering mechanisms of C3R through inhibition of lipid digestion and absorption in vitro. Methods The inhibitory activity of C3R against pancreatic lipase and cholesterol esterase was evaluated using enzymatic fluorometric and enzymatic colorimetric assays, respectively. An enzyme kinetic study using Michaelis-Menten and the derived Lineweaver-Burk plot was performed to understand the possible types of inhibition. The formation of cholesterol micelles was determined using the cholesterol assay kit. The bile acid binding was measured using the colorimetric assay. The NBD cholesterol uptake in Caco-2 cells was determined using fluorometric assay. The mRNA expression of cholesterol transporter (Niemann-Pick C1-like 1) was determined by RT-PCR. Results The results showed that C3R was a mixed-type competitive inhibitor of pancreatic lipase with the IC50 value of 59.4 ± 1.41 μM. Furthermore, C3R (0.125-1 mM) inhibited pancreatic cholesterol esterase about 5-18%. In addition, C3R inhibited the formation of cholesterol micelles and bound to primary and secondary bile acid. In Caco-2 cells, C3R (12.5-100 μM) exhibited a significant reduction in cholesterol uptake in both free cholesterol (17-41%) and mixed micelles (20-30%). Finally, C3R (100 μM) was able to suppress mRNA expression of NPC1L1 in Caco-2 cells after 24 h incubation. Conclusions The present findings suggest that C3R acts as a lipid-lowering agent through inhibition of lipid digestion and absorption.